Factors Associated With Condom Breakage During Anal Intercourse: A Cross-Sectional Study of Men Who Have Sex With Men Recruited in an Online Survey - Kim, Min (JMIR Public Health Surveill, 2016)
BACKGROUND: Within the United States, HIV affects men who have sex with men (MSM) disproportionally compared to the general population. In 2011, MSM represented nearly two-thirds of all new HIV infections while representing less than 2% of the US male population. Condoms continue to be the foundation of many HIV prevention programs; however, the failure rate of condoms during anal intercourse among MSM is estimated to be 0.5% to 8%, and condom breakages leave those affected at high risk for HIV transmission. OBJECTIVE: Estimate the frequency of condom breakage and associated demographic and behavioral factors during last act of anal intercourse using data from a national online HIV prevention survey of MSM. METHODS: From March 19 to April 16, 2009, data were collected on 9005 MSM through an online survey of US MSM recruited through a social networking site. Using multivariable logistic regression and controlling for several demographic and sexual risk behaviors, we estimated odds ratios of the association between condom breakage and several risk factors. RESULTS: In the study, 8063 participants reported having at least one male sexual partner in the last 12 months. The median age of participants was 21 years (range 18-65). More than two-thirds (68.2%, 5498/8063) reported anal intercourse during last sex and 16.90% (927/5498) reported using a condom during last anal intercourse act. Condom breakage was reported by 4.4% (28/635) participants who engaged in receptive anal intercourse and 3.5% (16/459) participants who engaged in insertive anal intercourse, with an overall failure rate of 4.0% (95% CI 3.2%-6.0%). Age (adjusted odds ratio [aOR] per 5 years: 0.53 (95% CI 0.30-0.94), number of male sex partners (aOR per 5 sex partners: 1.03 (95% CI 1.00-1.08), and being high or buzzed during sex with a casual sex partner (aOR: 3.14, 95% CI 1.02-9.60) were associated with condom breakage. CONCLUSIONS: Our results indicate condom breakage is an important problem for MSM that may be more common for younger men, for men with more partners, and during sex with casual partners after alcohol consumption or drug use. A better understanding of why condom breakage occurs more often in these groups is needed to improve educational efforts. Further, during this time of expanded interest in new condom designs, consideration should be given to how condom design might minimize breakage during anal sex.